Isolated pulmonary artery vasculitis - (:unkn) unknown (My University, 2020)
We present a unique case of a 26‑year‑old woman, which first evaluated as sarcoma or thromboembolic events with their clinical and radiological similarities of the pulmonary artery but diagnosed as isolated pulmonary artery vasculitis after endarterectomy with the help of histopathological examinations. After the endarterectomy procedure, the other causes that may lead to vasculitis had been excluded. The patient had the immunosuppressive therapy after the procedure, and her control computerized tomography revealed that the lumen of the pulmonary artery was wide open. Isolated pulmonary artery vasculitis must be considered as a differential diagnosis when a filling defect of the pulmonary artery had been detected without other systemic findings.